Prevalence of knee pain, radiographic osteoarthritis and arthroplasty in retired professional footballers compared to men in the general population: a cross-sectional study - Fernandes, Gwen Sascha; Parekh, Sanjay M.; Moses, Jonathan; Fuller, Colin; Scammell, Brigitte E.; Batt, Mark E.; Zhang, Weiya; Doherty, Michael (BMJ Publishing Group, 2017)
Objectives: To determine the prevalence of knee pain, radiographic knee osteoarthritis (RKOA), total knee replacement (TKR) and associated risk factors in male ex-professional footballers compared to men in the general population (comparison group). Methods: 1207 male ex-footballers and 4085 men in the general population in the UK were assessed by postal questionnaire. Current knee pain was defined as pain in or around the knees on most days of the previous month. Presence and severity of RKOA were assessed on standardised radiographs using the Nottingham Line Drawing Atlas (NLDA) in a sub-sample of 470 ex-footballers and 491 men in the comparison group. The adjusted risk ratio (aRR) and risk difference (aRD) with 95% confidence interval (CI) in ex-footballers compared to the general population were calculated using the marginal model in Stata. Results: Ex-footballers were more likely than the comparison group to have current knee pain [aRR 1.91, 95%CI 1.77-2.06], RKOA [aRR 2.21, 95%CI 1.92-2.54] and TKR (aRR 3.61, 95%CI 2.90–4.50). Ex-footballers were also more likely to present with chondrocalcinosis [aRR 3.41, 95%CI 2.44-4.77]. Prevalence of knee pain and RKOA were higher in ex-footballers at all ages. However, even after adjustment for significant knee injury and other risk factors, there was more than a doubling of risk of these outcomes in footballers. Conclusions: The prevalence of all knee osteoarthritis outcomes (knee pain, RKOA and TKR) were 2-3 times higher in male ex-footballers compared to men in the general population group. Knee injury is the main attributable risk factor. Even after adjustment for recognised risk factors, knee osteoarthritis appear to be an occupational hazard of professional football.